Future ecosystem changes in the Northeast Atlantic: a comparison between a global and a regional model system. (19th July 2018) - Skogen, Morten D; Hjøllo, Solfrid S; Sandø, Anne Britt; Tjiputra, Jerry
Abstract: The biogeochemistry from a global climate model (Norwegian Earth System Model) has been compared with results from a regional model (NORWECOM.E2E), where the regional model is forced by downscaled physics from the global model. The study should both be regarded as a direct comparison between a regional and its driving global model to investigate at what extent a global climate model can be used for regional studies, and a study of the future climate change in the Nordic and Barents Seas. The study concludes that the global and regional model compare well on trends, but many details are lost when a coarse resolution global model is used to assess climate impact on regional scale. The main difference between the two models is the timing of the spring bloom, and a non-exhaustive nutrient consumption in the global model in summer. The global model has a cold (in summer) and saline bias compared with climatology. This is both due to poorly resolved physical processes and oversimplified ecosystem parameterization. Through the downscaling the regional model is to some extent able to alleviate the bias in the physical fields, and the timing of the spring bloom is close to observations. The summer nutrient minimum is one month early. There is no trend in future primary production in any of the models, and the trends in modelled pH and Ω Ar are also the same in both models. The largest discrepancy in the future projection is in the development of the CO2 uptake, where the regional suggests a slightly reduced uptake in the future.